Solving preemptive job-shop scheduling problems using a true concurrency model. (2016) - Arfi, Farid; Ilié, Jean-Michel; Saidouni, Djamel-Eddine
A true concurrency model called stopwatch durational action timed automata (S-DATA) is proposed to model preemptive timed concurrent systems. We demonstrate its usefulness in tackling the preemptive job-shop scheduling problem (PJSSP). This yields a compact reachability tree representing the possible schedules such that the durations and preemptions of the scheduled actions are dynamically managed. Different techniques are demonstrated to reduce the space search over such reachability tree, preserving the optimal schedules of the problem. The efficiency of approach is tested on a number of well-known benchmark problems and compared with the best method of scheduling in common use.